The role of a moisture-barrier latex in controlling retention, stability and release of D-limonene from complex coacervated matrix microparticles formed during spray drying - Tang, Yuting; Park, Hayeon; Scher, Herbert B.; Jeoh, Tina (Frontiers in Nutrition, 2022)
Limonene from citrus peel oil is valued as fragrance and flavor additives in food and beverages; however, D-limonene is highly volatile and oxygen-sensitive, thus present storage and stability challenges in food products. A novel, industrially-scalable microencapsulation by in situ complex coacervation during spray drying process (CoCo process) was applied to encapsulate limonene in alginate-gelatin matrix microparticles. Specifically, we investigated the potential to improve upon prior work demonstrating volatile retention and enteric release of limonene from the complex coacervated (CoCo) microcapsules by incorporating ethylcellulose to improve moisture and oxygen barrier properties of the encapsulation matrix. We hypothesized that ethylcellulose, commonly used as a water-barrier coating with pharmaceuticals, would enhance the ability of CoCo microcapsules to retain and shelf-stabilize limonene. The CoCo process alone could achieve limonene retention of 77.7%±1.3% during spray drying, with only 10% limonene loss and low oxidation rate after 3-weeks of storage in ambient conditions. Contrary to expectations, incorporating ethylcellulose with the CoCo formulation increased volatile losses of limonene during spray drying and during prolonged storage. Moreover, CoCo powders with ethylcellulose accelerated limonene release in water and simulated gastric fluid, and decelerated release in simulated intestinal fluid – a result that was contrary to targeting enteric release. Instead of simply forming a protective water barrier film in the microparticles during spray drying as envisioned, ethylcellulose appeared to bring limonene to the particle surfaces, thereby enhancing volatile losses, facilitating oxidation and accelerating release in acidic aqueous media. Using ethylcellulose as a model, this study demonstrated the potential to formulate CoCo microparticles using latex excipients to control burst release of the payload followed by long-lasting sustained release in air and in aqueous environments.